(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The TNF-a gene considered as strong candidate for immune modulator and pro inflammatory cytokine responsible for genetic susceptibility of chronic disease such as the initiation and development of inflammatory bowel disease (IBD).The aim of this study is to investigate the genetic polymorphisms of -1031 in TNF-a gene with susceptibility of Iraqi IBD patients Method: The total number of this study 95 blood samples (75 Iraqi IBD patients and 20 from healthy individuals as a control group). The genetic polymorphisms in TNF-a-1031 gene was investigated using restriction fragment length polymorphism (RFLP) and Sanger sequences techniques. Results: The genotype allele frequency of -1031 polymorphism was significantly higher in CD Iraqi patients (P=0.042 , Chi 4.612. OR= 0.72-1.64) ,C allele may be have protective role , whereas the T allele may increase susceptibility to IBD. In conclusion: The TNF-a -1031 gene polymorphisms in promoter region have an important role in the occurrence of inflammatory bowel disease of Iraqi population especially in CD patients although some results didn’t give us a significant differences.It’s possible that C allele may be have protective role , whereas the T allele may increase susceptibility to IBD